Research on Sensitive Information Protection of Carriers' Big-Data Platform - Wenyu Pan; Xin Cai; Yilong Ruan; Xiaohui Yao (Dianxin kexue)
The scope of sensitive information of carriers' big-data platform was discussed. The methods to protect sensitive information were described. The key technologies and mainstream technical methods in the field of research were summarized. Based on the layered architecture of carries big-data platform, technical solutions for different sensitive information protection technology were designed.